Physiological cost and thermal envelope: A novel approach to cycle garment evaluation during a representative protocol - Corbett, J.; Barwood, M. J.; Tipton, M. J. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study aimed to examine thermoregulation in different clothing assemblies during a representative cycling exercise protocol. Six men undertook cycling exercise simulating representative thermal exchange challenges while wearing low (LOW), intermediate (INT1 and INT2), or high (HI) amounts of clothing. Exercise was conducted at 14.5 °C, 46.8% relative humidity and included a "flat" [45 min at 35% peak power output (PPO), wind speed 8.3?m/s], "uphill" (30 min at 55% PPO, wind speed 3.6?m/s), and "downhill" (20 min at 50 W, wind speed 16.7 m/s) stage. Rectal temperature changed with the exercise stage and was independent of clothing assembly. In contrast, an "envelope" was evident for mean body temperature, resulting from differences in mean skin temperature between the LOW and HI conditions. The elevated mean body temperature in HI was associated with increased physiological "cost," in the form of increased sweat production and heart rate. Physiological cost provides a better index of clothing performance than deep body temperature in the "thermoregulatory zone," as a consequence sports clothing should attempt to optimize the balance between comfort and reduced physiological cost.